1994
DOI: 10.1071/mf9941157
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical systematics of the marine fish family Centrolophidae (Teleostei:Stromateoidei) from Australian waters

Abstract: The phylogenetic relationships of 11 stromateoid species (nine from the Family Centrolophidae and one each from the Nomeidae and Tetragonuridae) were examined by allozyme electrophoresis. Data from 30 loci were used for three phylogenetic analyses. Two phenetic trees were derived: a UPGMA tree derived from Nei's unbiased genetic distance, and a distance-Wagner tree based on modified Rogers' distances. A cladistic analysis, using maximum parsimony, was also carried out with loci as characters and alleles as uno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Thirteen species have been reported from the Red Sea region, belonging to three genera: Mulloides Bleeker, 1849, Parupeneus Bleeker, 1863 and Upeneus Cuvier, 1829. Electrophoretic analysis can add a different dimension, which provides insight into the interrelationship of species and genera, to these taxonomic studies (Avise, 1974;Buth, 1984;Bolch et al, 1994). Regarding the Red Sea Mullidae, electrophoretic studies may be of particular interest, since two members of this family, the brownband goatfish Upeneus pori Ben-Tuvia and Golani, 1989 (previously known in this area as U. asymmetricus), and the goldband goatfish, Upeneus SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen species have been reported from the Red Sea region, belonging to three genera: Mulloides Bleeker, 1849, Parupeneus Bleeker, 1863 and Upeneus Cuvier, 1829. Electrophoretic analysis can add a different dimension, which provides insight into the interrelationship of species and genera, to these taxonomic studies (Avise, 1974;Buth, 1984;Bolch et al, 1994). Regarding the Red Sea Mullidae, electrophoretic studies may be of particular interest, since two members of this family, the brownband goatfish Upeneus pori Ben-Tuvia and Golani, 1989 (previously known in this area as U. asymmetricus), and the goldband goatfish, Upeneus SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies of fi shes found no genetic differentiation between seamount and nearby non-seamount populations: the trevalla Hyperoglyphe antarctica around Australia (Bolch et al, 1994), a boarfi sh species (Pentacerotidae) on the Hawaiian chain (Borets, 1980), and the alfonsino Beryx splendens in the southwest Pacifi c (Hoarau and Borsa, 2000). Two other studies looked at the genetics of seamount populations and found no differentiation, but could not be certain that the sequences used had suffi cient mutation rates for recent speciation to be found: France and Hoover (2002) for octocorals of the subclass Octocorallia, and Smith et al (2004) for the bamboo coral Keratoisis, also an octocoral.…”
Section: Genetic Evidencementioning
confidence: 99%
“…S. ovalis and S. velaini) and the other is weak-spined and soft-fleshed (e.g. S. medusophagus and S. huttoni) [17,25]. Thus, the breadth and validity of the genus has been debated by various authors [e.g.…”
Section: Seriolella Punctata 91mentioning
confidence: 99%
“…[26][27][28]. In this context, an allozyme survey of 11 stromateoid species from Australian waters [25], including two Schedophilus species, clearly evidenced the separate clustering of the weakspined S. huttoni and the hard-spined S. labyrinthicus, and the non monophyly of the genus. Bolch et al [25] therefore proposed reconsidering the composition of the genus and suggested that the hard-spined, firm-fleshed group might be more correctly represented as a distinct centrolophid genus.…”
Section: Seriolella Punctata 91mentioning
confidence: 99%
See 1 more Smart Citation